1989
DOI: 10.1016/0735-1097(89)90229-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired coronary vasodilator reserve in the immediate postcoronary angioplasty period: Analysis of coronary artery flow velocity indexes and regional cardiac venous efflux

Abstract: The ratio of peak hyperemic/basal mean coronary flow velocity, an index of coronary vasodilator reserve, immediately after coronary angioplasty normalizes in less than 50% of patients. To evaluate other indexes of coronary vasodilator capacity, both intracoronary arterial velocity and cardiac venous efflux were measured at rest and during vasodilator-induced coronary hyperemia (intracoronary nitroglycerin and papaverine) before and after angioplasty in 27 patients; 17 patients had measurements of intracoronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(36 citation statements)
references
References 51 publications
1
34
0
1
Order By: Relevance
“…[15][16][17] This increase in baseline flow velocity was repeatedly ascribed to disturbed coronary autoregulation. 15,17 Under physiological circumstances, coronary autoregulation regulates vasodilation and vasoconstriction of the coronary resistance vessels to maintain stable coronary blood flow to the distal myocardium within a physiological range of perfusion pressures.…”
Section: Interpretation Of Impaired Reference Vessel Cfvr In the Presmentioning
confidence: 99%
“…[15][16][17] This increase in baseline flow velocity was repeatedly ascribed to disturbed coronary autoregulation. 15,17 Under physiological circumstances, coronary autoregulation regulates vasodilation and vasoconstriction of the coronary resistance vessels to maintain stable coronary blood flow to the distal myocardium within a physiological range of perfusion pressures.…”
Section: Interpretation Of Impaired Reference Vessel Cfvr In the Presmentioning
confidence: 99%
“…16 The pharmacological blockade of this inappropriate vasoconstriction would restore residual coronary flow reserve to its maximum value, but different drugs might be required for blocking epicardial arteries and small vessel constriction. Indeed, about 50% of the patients with stable coronary disease continue to have angina and positive exercise tests in spite of successful coronary interventional revascularization, 17,18 which does not appear to have significant impact on prognosis in these patients. 19 …”
Section: Chronic Stable Anginamentioning
confidence: 99%
“…These findings are in accordance with other studies that demonstrated an impaired coronary flow reserve immediately after balloon angioplasty, compared with normal values of the control group, due to an increased baseline coronary blood flow. 10,16 Several mechanisms have been postulated for the observed increase in baseline flow velocity after PTCA, such as (1) failure of the peripheral arterial vascular bed to vasoconstrict appropriately on the sudden increase in distal coronary pressure produced by coronary angioplasty, (2) epicardial vasoconstriction at the site of the Doppler guidewire tip mediated by a myogenic response and/or neural mechanisms, 17,18 or (3) the influence of drug therapy. 19,20 However, all patients were treated with nitroglycerin during the procedure, and there was no difference in drug therapy (nitrates, calcium antagonists, ␤-blockers, or ACE inhibitors) between patients with and without impaired CFR after PTCA.…”
Section: 6mentioning
confidence: 99%